Инфракрасные отрезающие фильтры на основе монокристаллов CdSb, ZnSb для оптофотоэлектронных устройств - Ashcheulov, A. A.; Gritsyuk, B. N.; Strebezhev, V. N. (PE "Politekhperiodika", Book and Journal Publishers, 2009)
Interference-absorption filters based on semiconductor crystals CdSb and ZnSb are proposed. Modeling of interference multilayer coating designs has been carried out, demonstrating the prospects for the development and practical application of CdSb-based cut-off filters with optimized parameters. Experimental results are presented, showing high optical characteristics and mechanical strength of two-channel CdSb-based cut-off filters intended for use in various optoelectronic devices.